Detecting Autologous Blood Transfusion in Doping Control: Biomarkers of Blood Aging and Storage Measured by Flow Cytofluorimetry - Donati, Francesco; Acciarini, Roberta; De Benedittis, Ilenia; de la Torre, Xavier; Pirri, Daniela; Prete, Mariangela; Stampella, Alessandra; Vernucci, Enza; Botre, Francesco (Current Pharmaceutical Biotechnology, 2018)
Background: Blood transfusions are banned by the World Anti-Doping Agency as a form of “blood doping”. A method of detection of homologous blood transfusion (HBT) has been implemented by the accredited anti-doping laboratories worldwide; however, no internationally recognized method has been finalized so far for the direct detection of autologous blood transfusions, which can at present be revealed only by targeted longitudinal profiling of key blood parameters. Methods: The present article reports the results of an investigation aimed to pre-select potential biomarkers of blood aging and storage that can be measured to identify the presence in the sample of reinfused blood. Microparticles from platelets and erythrocytes, erythrocytes size and density, annexin V (as a marker of phosphatidylserine externalization), and the membrane surface antigens CD 55 and CD 59, were specifically considered as potential biomarkers and measured by flow cytofluorimetric techniques. Results and Conclusion: Our results indicate that the parameters more strongly affected by the ex vivo storage of whole blood are erythrocytes size and density, annexin V and microparticles. Although the real diagnostic value of the proposed biomarkers shall obviously be confirmed by further studies carried out on blood samples collected after an actual autologous blood transfusion, these results appear very encouraging towards the development of a direct method for detecting autologous blood transfusion in sport doping.
Keywords: Autologous blood transfusions